Plan de negocios para la creación de un asadero restaurante para la comercialización de brochetas, cantón Quevedo, año 2014. - Vásquez Castro, Germán Gabriel (2015)
This research entitled "Business Plan for the establishment of a steakhouse restaurant dedicated to the marketing of the center of the kebabs in 2014 Quevedo Canton." Is based on the urgent need to best meet the needs of consumers. Seeking to answer several questions, the following research question was raised How affects the creation of a microenterprise Restaurant (steakhouse spitful) in Canton Quevedo? This led us to propose the following objectives; 1 "Conduct a market for supply and demand as well as the tastes and preferences of the targeted segment." 2 "Conduct a technical study to determine the location and size of the project, initial and other requirements according to the type of investment project". 3 "To demonstrate the feasibility of the project through an economic and financial study." "The assumptions underlying this research are: General Hypothesis "Creating a Business Plan will provide the right tools and systems for the implementation of a steakhouse restaurant in the city of Quevedo, generating competitiveness and profitability?". In developing the theoretical framework were taken as reference the main variables of the assumptions such as association, organizations, market research, economic analysis, Technical study, etc.. In terms of methodology, analytic, deductive methods were applied, the type of field research and literature was a survey, and applying a statistical formulation results threw us to survey 246 people. Among the most relevant results, we can mention that 100% of respondents if they agree on a super skewer made eating pork, shrimp, fish and sausage accompanied by a rich salad and fried yucca.